2015
DOI: 10.1007/s10853-015-9561-4
|View full text |Cite
|
Sign up to set email alerts
|

Tensile-stress-induced growth of ellipsoidal ω-precipitates in a Ti–20wt%Mo alloy

Abstract: The effects of applied tensile stress on the growth of ellipsoidal ω phase precipitates have been investigated for a Ti−20wt%Mo alloy aged at 300 °C. The application of tensile stress accelerates the growth of ω-precipitates when the misfit strain ε Μ of the precipitates along the loading direction is greater than 0; however, it does not significantly affect the growth of precipitates in cases where ε Μ < 0. Whereas the growth of precipitates under no stress or in the case where ε Μ < 0 under tensile stress is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
2
8
1
Order By: Relevance
“…As in our previous study [9], we often observed grains in which the (113) β plane was nearly parallel to the surfaces of TEM thin foils. The grains in which the (113) β plane was parallel to the specimen surfaces were used to estimate the misfit strains of the variants I and II, among the four possible ω-variants, along the LD on (113) β (see Fig.…”
Section: Estimate Of Misfit Strainsupporting
confidence: 81%
See 4 more Smart Citations
“…As in our previous study [9], we often observed grains in which the (113) β plane was nearly parallel to the surfaces of TEM thin foils. The grains in which the (113) β plane was parallel to the specimen surfaces were used to estimate the misfit strains of the variants I and II, among the four possible ω-variants, along the LD on (113) β (see Fig.…”
Section: Estimate Of Misfit Strainsupporting
confidence: 81%
“…We have observed the compressivestress-induced growth of ω-precipitates in the case ε Μ < 0, which is in contrast with the tensile-stress-induced growth of the precipitates in the case ε Μ > 0 [9], and further found the lower velocity of the interface-controlled growth of ω-precipitates in the case ε Μ < 0 under a compressive stress of 450 − 550 MPa than the velocity of the interface-controlled growth of ω-precipitates in the case ε Μ > 0 under the same tensile stress, as will be shown later.…”
Section: Introductioncontrasting
confidence: 64%
See 3 more Smart Citations